What do people learn from following the news? A diary study on the influence of media use on knowledge of current news stories. (June 2021) - Beckers, Kathleen; Van Aelst, Peter; Verhoest, Pascal; d'Haenens, Leen
One of the main functions of news media in democracies is informing the citizenry on day-to-day affairs. However, the way in which citizens gather news has changed as nowadays people have more opportunities than ever before to adapt their media consumption based on their preferences. One of the major game changers was the introduction of social media. This raises the question to what extent traditional media still contribute to people's knowledge of current affairs. Using a time-diary study in the Flemish media context, we investigate the influence of different forms of news consumption on current news knowledge. We conclude that traditional (print and audiovisual) media, including popular outlets, continue to be the major contributors to people's knowledge about current affairs and that social media hardly contribute at all.